"The Pit and the Pond": Hydraulic Projects and Municipal Rights in Modern Palestine. Issue 4 (11th November 2022) - Abusaada, Nadi
Abstract: The rationalization of urban water-supply systems and networks was a pressing concern in the development of modern cities globally in the late nineteenth and early twentieth centuries. The rise of the modern city did not manifest only in the complete overhaul of water and sewage infrastructures but also in the creation of new mechanisms of urban governance to manage them. Examining understudied municipal water projects in Jaffa and Nablus, two chief centers of light industry in the late Ottoman and Mandate eras, this paper provides an analysis of the historical relationship between urban governance and urban infrastructures in modern Palestine. It investigates the involvement of Palestinian urbanites in the debates over municipal water projects in their cities, demonstrating that these constituted more than merely utilitarian instruments and were foundational to the articulation of urban rights in modern Palestine.